Isolation, Screening, and Identification of Novel Isolates of Actinomycetes from India for Antimicrobial Applications - Singh, Vineeta; Haque, Shafiul; Singh, Harshita; Verma, Jyoti; Vibha, Kumari; Singh, Rajbir; Jawed, Arshad; Tripathi, C. K. M. (Frontiers in Microbiology, 2016)
The search for novel bioactive compounds from the natural environment has been rapidly increased with the increase in multi-drug resistant (MDR) pathogens. In the present study, the antimicrobial potential of novel actinomycetes has been evaluated by initial screening of six soil samples. Primary and secondary screening was performed against Bacillus subtilis, Staphylococcus aureus, Escherichia coli, Candida albicans, Candida tropicalis, Trichophyton rubrum, and other MDR bacterial and fungal test strains, and at the end thirteen active isolates were selected for further study. Microbial strains were identified on the basis of growth conditions and other biochemical characters. Five most active microbial strains were identified using 16S rRNA sequence homology and designated as Streptomyces xanthophaeus MTCC 11938, Streptomyces variabilis MTCC 12266, Streptomyces xanthochromogenes MTCC 11937, Streptomyces levis EU 124569 and Streptomyces sp. NCIM 5500. Four antibacterial and three antifungal compounds isolated from the above five isolates were purified and partially characterized using UV absorption and IR spectra. Two antibacterial metabolites, belong to chromone and peptide antibiotic, respectively. The antifungal compounds were found to be of non-polyene nature. In conclusion, we study the isolation of novel bacterial strains of actinomycetes for producing novel compounds having antibacterial and antifungal activities from the unexplored agro-ecological niches of India. Also, this study paves the way for further characterization of these isolates of Streptomyces sp. for their optimum utilization for antimicrobial purposes.